PALEMBANG HARUM : PROMOSI & BRANDING KULINER PALEMBANG DI MEDIA SOSIAL - Nouvi Ayu Pertiwi; Rahma Santhi Zinaida (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
This research titled is Palembang Harum : Palembang Culinary Branding and Ppromotion in Social Media. The purpose of this reasearch is to know and describe marketing communication carried out the store Palembang Harum. through social media. This research using internet marketing theory and marketing mix. The object of this research is Palembang Harum. A subject in this research is the owner, and a store clerk. Data collection techniques used observation, interview, and documentation. This research result can be concluded that marketing communications conducted by Palembang Harum through social media is in the form of a promotion such a hold giveaway, posted a picture, hold the discount, and endorsement.